Guido Mazzoni. On Modern Poetry. Translated by Zakiya Hanafi. Belknap Press, 2022. - Anthony DeGenaro (Studies in 20th & 21st Century Literature, 2023)
Review of Guido Mazzoni. On Modern Poetry. Translated by Zakiya Hanafi. Belknap Press, 2022. 294 pp.
Keywords: poetry; genre analysis; modern poetry; modern literature; Italian literature